Heat transfer enhancement from a heated plate with hemispherical convex dimples by forced convection along with a cross flow jet impingement - Garnayak, Subrat; Patro, Pandab (Zielona Góra: Uniwersytet Zielonogórski)
In the present study, heat transfer from a small three dimensional rectangular channel due to turbulent jet impinging from a nozzle normal to the main flow at the inlet has been investigated.
Keywords: heat transfer enhancement; jet impingement; convex dimpled surface; SST k-w model; cross flow